If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 6q(5 + -1q) = 0 12 + (5 * 6q + -1q * 6q) = 0 12 + (30q + -6q2) = 0 Solving 12 + 30q + -6q2 = 0 Solving for variable 'q'. Factor out the Greatest Common Factor (GCF), '6'. 6(2 + 5q + -1q2) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(2 + 5q + -1q2)' equal to zero and attempt to solve: Simplifying 2 + 5q + -1q2 = 0 Solving 2 + 5q + -1q2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -2 + -5q + q2 = 0 Move the constant term to the right: Add '2' to each side of the equation. -2 + -5q + 2 + q2 = 0 + 2 Reorder the terms: -2 + 2 + -5q + q2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5q + q2 = 0 + 2 -5q + q2 = 0 + 2 Combine like terms: 0 + 2 = 2 -5q + q2 = 2 The q term is -5q. Take half its coefficient (-2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. -5q + 6.25 + q2 = 2 + 6.25 Reorder the terms: 6.25 + -5q + q2 = 2 + 6.25 Combine like terms: 2 + 6.25 = 8.25 6.25 + -5q + q2 = 8.25 Factor a perfect square on the left side: (q + -2.5)(q + -2.5) = 8.25 Calculate the square root of the right side: 2.872281323 Break this problem into two subproblems by setting (q + -2.5) equal to 2.872281323 and -2.872281323.Subproblem 1
q + -2.5 = 2.872281323 Simplifying q + -2.5 = 2.872281323 Reorder the terms: -2.5 + q = 2.872281323 Solving -2.5 + q = 2.872281323 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + q = 2.872281323 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + q = 2.872281323 + 2.5 q = 2.872281323 + 2.5 Combine like terms: 2.872281323 + 2.5 = 5.372281323 q = 5.372281323 Simplifying q = 5.372281323Subproblem 2
q + -2.5 = -2.872281323 Simplifying q + -2.5 = -2.872281323 Reorder the terms: -2.5 + q = -2.872281323 Solving -2.5 + q = -2.872281323 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + q = -2.872281323 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + q = -2.872281323 + 2.5 q = -2.872281323 + 2.5 Combine like terms: -2.872281323 + 2.5 = -0.372281323 q = -0.372281323 Simplifying q = -0.372281323Solution
The solution to the problem is based on the solutions from the subproblems. q = {5.372281323, -0.372281323}Solution
q = {5.372281323, -0.372281323}
| -(1+6k)+4k=-8k-7(k+2) | | 117=8x+57 | | x+-5.5-4(5)=-18 | | 6x^3+11x^2-92x+15=3 | | 4y+5=-17 | | 6x^3+11x^2-92x+15=0 | | 3x-4=42 | | x^2-22x+121=144 | | 751-12=x | | -4(2-3p)=40+4p | | 238+419=x | | x-3=6x-7 | | x+5=14x | | 18x^2+44x=11x-30 | | (-1x)+(-1)= | | x=.5x*2 | | x^2-4x+4=1000 | | 5-6ln(x)=9 | | 3(6-z)-30=21z-4(3+6) | | x*-x=x | | -0.2x+6.61=-0.7x+2.11 | | 91=c+52 | | 6x+15d=720 | | 4=3x-4 | | a+(a-4)=(a+5)-(a+2) | | -.25x-50=-100 | | -3(2x+5)=x-7x-15 | | -0.25x-50=-75 | | 7x+4x-9x=4+2 | | 160+1e=100+5e | | 2x-2=-.5x+3 | | -6x+3=6x-4 |